Protectants used in the cryopreservation of microorganisms - Hubálek, Zdenek (Cryobiology, 2003)
The cryoprotective additives (CPAs) used in the frozen storage of microorganisms (viruses, bacteria, fungi, algae, and protozoa) include a variety of simple and more complex chemical compounds, but only a few of them have been used widely and with satisfactory results: these include dimethylsulfoxide (Me2SO), glycerol, blood serum or serum albumin, skimmed milk, peptone, yeast extract, saccharose, glucose, methanol, polyvinylpyrrolidone (PVP), sorbitol, and malt extract. Pairwise comparisons of the cryoprotective activity of the more common CPAs used in cryomicrobiology, based on published experimental reports, indicate that the most successful CPAs have been Me2SO, methanol, ethylene glycol, propylene glycol, and serum or serum albumin, while glycerol, polyethylene glycol, PVP, and sucrose are less successful, and other sugars, dextran, hydroxyethyl starch, sorbitol, and milk are the least effective. However, diols (as well as some other CPAs) are toxic for many microbes. Me2SO might be regarded as the most universally useful CPA, although certain other CPAs can sometimes yield better recoveries with particular organisms. The best CPA, or combination of CPAs, and the optimum concentration for a particular cryosensitive microorganism has to be determined empirically. This review aims to provide a summary of the main experimental findings with a wide range of additives and organisms. A brief discussion of mechanisms of CPA action is also included.
Keywords: Cryoprotective Agents; kryoprezervace; kryoprotektivní látky; Cryopreservation; Microbiological Techniques; mikrobiologické techniky